Analysis of Cardiovascular Hemodynamic and Autonomic Variables in Individuals with Systemic Arterial Hypertension, Type 2 Diabetes Mellitus, and Parkinson’s Disease: A Comparative Study - Yuphiwa Ngomane, Awassi [UNESP]; Martins de Abreu, Raphael; Fernandes, Bianca [UNESP]; Roque Marçal, Isabela [UNESP]; Veiga Guimarães, Guilherme; Gomes Ciolac, Emmanuel [UNESP] (My University, 2022)
Background: Systemic arterial hypertension (SAH), type 2 diabetes mellitus (T2DM), and Parkinson’s disease (PD) are highly prevalent chronic diseases that can significantly impact the cardiovascular system. Aim: The aim of this study was to compare hemodynamic and autonomic variables at rest in individuals with SAH, T2DM, or PD. Methods: Fifty sedentary or insufficiently active individuals (22 men) with SAH (age = 66 ± 5.0 yr), T2DM (age = 52 ± 10 yr) or PD (age = 68 ± 8.0 yr) had their resting blood pressure (BP), arterial stiffness, endothelial function, and heart rate variability (HRV) assessed and compared. Results: Systolic and diastolic BP were higher in SAH (130 ± 10 / 80 ± 10 mmHg) than T2DM (110 ± 14 / 75 ± 11 mmHg) and PD, and (123 ± 20 / 70 ± 11 mmHg) respectively. T2DM individuals showed lower arterial stiffness (8.4 ± 1.1 m/s), when compared to SAH (10.3 ± 2.3 m/s) and PD (10.6 ± 3.0 m/s). T2DM had greater resting tachycardia showed by the mean RR (759 ± 79 ms), than SAH (962 ± 169 ms) and PD (976 ± 134 ms), which was accompanied by higher sympathetic modulation (low frequency [LF]: 62 ± 19 nu) and lower parasympathetic modulation (high frequency [HF]: 32 ± 16 nu) when compared to SAH (LF: 40 ± 16 nu; HF: 61 ± 33 nu). No differences among groups were found on non-linear HRV markers and endothelial reactivity indexes. Conclusions: Individuals with T2DM showed impaired levels of cardiac autonomic markers when compared to individuals with SAH and PD, despite of having lower levels of BP and arterial stiffness.
Keywords: Arterial pressure; cardiac control; chronic disease; endothelium; heart rate